Determination of cadmium and lead in green mussel of Pantai Lido and Sungai Pendas coastal area - Amirul Syuhada Jamaludin, 1988-; Jafariah Jaafar; Fakulti Sains (2010)
Project Paper (Sarjana Muda Sains (Kimia Industri)) - Universiti Teknologi Malaysia, 2010